Professional skills required by companies in Tarapoto - Siles Nates, Mario Manuel (2013)
This article aims to present a descriptive survey results on skills most in demand in the city of Tarapoto, San Martin, Peru, conducted in 108 companies also develop a sectoral analysis of the companies that are attached to Chamber of Commerce of San Martin. These competencies were grouped into five categories: personal management skills, management, teamwork, influence, cognitive achievement and values, practice of values. Among the results is the supremacy of teamwork skills that group skills, problem solving, leadership, empathy, naturalness, and teamwork. Followed by the practice of the values and skills of influence. These being the three largest clusters demand prioritization and professionals workin in the mentioned companies currently.